Electro-osmotic properties and effects of pH on geotechnical behaviour of peat - Asadi, Afshin (2010)
Peat is an accumulation of partially decayed vegetation matter with high non-crystalline colloid which is formed in wetland systems. Using electro-osmotic techniques to improve peat entails developing a fundamental understanding of the electro-osmotic environment in peat which is an excellent context for this study. Electro-osmotic properties, electro-osmotic experiments, and the physicochemical effects on the peat due to electro-osmotic treatment were investigated. In addition, chemico-geomechanical sensitivities of peat to pH gradients were examined. The electro-osmotic properties of peat in the presence of different cations were also modeled by means of artificial neural networks.